(23) Krisis Keuangan Daerah dan Administrasi Publik Lokal: Mencari Solusi untuk Kelangsungan Keuangan Pemerintah Daerah - Agus, Nour Farozi; Ridianto, Ridianto; Valentina, Devince Suci; Ramdani, Vidi (SENGKUNI Journal (Social Science and Humanities Studies), 2023)
The local financial crisis has become a major concern in local public administration in various countries. This article outlines the main challenges that local governments face in maintaining their financial sustainability. In this context, various solutions and strategies that can be applied to overcome the local financial crisis are discussed, including improved budget management efficiency, diversification of revenue sources, and inter-local government cooperation. These efforts are key in ensuring that local governments can continue to provide essential services to their communities while overcoming financial cons.